Relationship Between Hygiene Factors and Motivation Factors With The Work Motivation Of Nurses in First-Level Health Facilities - Mhd. Latief Shihab Lubis; Al Muntazar (Open Access Health Scientific Journal, 2026)
Background: Work motivation is one of the factors that can affect nurses in providing health services to the community optimally. Incentives and recognition are still problems related to nurses' motivation at work. This study aimed to find out the factors that affect the work motivation of nurses in the Ciputat and East Ciputat District Health Centers in 2022. This study uses a quantitative approach.Methods: The study design in this study is Cross sectional and the total sampling method with a sample of 62 people. The distribution of the frequency of work motivation of nurses in health centers includes high work motivation of 72.6%.Result: There is a relationship between the variables of remuneration, work environment conditions, job security/sense of security, individual relationships, recognition, work, and self-development with the work motivation of nurses at the Ciputat and East Ciputat District Health Centers in 2022. the more it will increase the motivation of nurses at work.Discussion: It is hoped that the health center will be able to implement supervision efforts well, give awards to nurses who achieve an achievement in order to increase the motivation of nurses in work.